Design Principles for the Enhanced Transparency Range of Correlated Transparent Conductors. Issue 5 (8th March 2021) - Ha, Youngkyoung; Byun, Jinho; Lee, Jaekwang; Lee, Shinbuhm
Abstract: Correlated transparent conductors (TCs) have attracted great attention because they can overcome the limitations of conventional TCs owing to their high visible transmittance and low sheet resistance. However, the most widely studied TC 3 d 1 SrVO3 exhibits low ultraviolet transmittance, and the recently investigated TC 4 d 2 SrMoO3 has low infrared transmittance. Here, it is proposed that the wide transparency range of correlated TCs arises from both high correlation strength and high transition energy from the O‐2 p to the transition metal d orbitals. Applying this comprehensive design principle to single‐crystalline correlated metals, it is confirmed that correlated 4 d 1 SrNbO3 exhibits enhanced ultraviolet–visible–infrared transmittance, with low sheet resistance at room temperature, compared to 3 d 1 SrVO3 and 4 d 2 SrMoO3 . Spectroscopic ellipsometry, X‐ray photoelectron spectroscopy, and density functional theory calculations reveal that the advantageous properties of 4 d 1 SrNbO3 can be attributed to high p – d transition energy and moderate correlation effect. The design principle can aid the discovery of additional high‐performance TC materials and further development of correlated TCs. Abstract : It is proposed that correlated transparent conductors have a wide transparency range when they exhibit both strong electron correlation and high transition energy from O‐2 p to transition metal d orbitals. Based on this design principle, a new correlated metal 4 d 1 SrNbO3 is discovered, whose transparent conductor performance surpasses those of 4 d 2 SrMoO3 and 3 d 1 SrVO3 .